2005
DOI: 10.1086/497064
|View full text |Cite
|
Sign up to set email alerts
|

The Polarization Signature of Extrasolar Planet Transiting Cool Dwarfs

Abstract: We investigate the linear polarization in the light of extrasolar planetary systems that may arise as a result of an occultation of the star by a transiting planet. Such an occultation breaks any spherical symmetry over the projected stellar disk and thus results in a non-vanishing linear polarization. This polarization will furthermore vary as the occultation progresses. We present both analytical and numerical results for the occultation of G-K-M-T dwarf stars by planets with sizes ranging from the one of Ea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 17 publications
5
44
0
Order By: Relevance
“…Associated with maximum fluxes from HD 189733b that are not located at maximal planetary elongations, the net diluted polarization degree peaks at orbital phases +0.35 and +0.65. The highest degrees of P are of the order of 0.0025 ± 0.0002 % at 0.7 keV, similarly to the polarization found in the optical band (Carciofi & Magalhães 2005).…”
Section: Polarizationsupporting
confidence: 67%
See 1 more Smart Citation
“…Associated with maximum fluxes from HD 189733b that are not located at maximal planetary elongations, the net diluted polarization degree peaks at orbital phases +0.35 and +0.65. The highest degrees of P are of the order of 0.0025 ± 0.0002 % at 0.7 keV, similarly to the polarization found in the optical band (Carciofi & Magalhães 2005).…”
Section: Polarizationsupporting
confidence: 67%
“…These results can be achieved thanks to radial velocity measurements, orbital brightness modulations, gravitational microlensing, direct imaging, astrometry, and polarimetry. The later is probably one of the most delicate methods since the anticipated white light polarization degree (about 10 −5 , Carciofi & Magalhães 2005;Kostogryz et al 2014;Kopparla et al 2016) resulting from scattering of stellar photons onto the atmospheric layers of Hot frederic.marin@astro.unistra.fr 1 In December 2016, 2695 planets out of a total of 3547 have been discovered by transit techniques, see http://exoplanet.eu/ Jupiters is expected to be just about detectable given the current limits of current optical, broad-band, stellar polarimeters (Schmid et al 2005;Hough et al 2006;Wiktorowicz 2009). Berdyugina et al (2008Berdyugina et al ( , 2011 reported to have successfully achieved a B-band polarimetric detection of HD 189733b and found a peak polarization of 2×10 −4 (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Stellar discs have a centrosymmetric polarization pattern due to light scattering (Leroy 2000), with maximum polarization very close to the limb of the star. In a uniform, spherically symmetric star the net polarization will be zero but star‐spots near the limb can produce a measurable polarization by breaking the symmetry, see Carciofi & Magalhães (2005).…”
Section: Resultsmentioning
confidence: 99%
“…The value of this polarization is maximal when the planet is crossing the edge of the source (Carciofi & Magalhães 2005;Wiktorowicz & Laughlin 2014;Kostogryz et al 2015). However, the occultation happens for phase angles greater than 90…”
Section: Polarization Due To the Stellar Occultation By Planetmentioning
confidence: 97%